Influence of the social and sporting context on the development of Spanish Paralympic athletes - Cerrada-Nogales, J. A.; Fernández-González, A.; Rodríguez, M.; Giménez, F. J.; Abad, M. T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction Whether an athlete reaches the highest level in any discipline will be determined by many factors. In the performance of Paralympic athletes, it is of paramount importance to understand the sporting context (Blauwt and Lezzoni, 2014) as they face numerous social and environmental barriers (Díaz et al., 2019) that limit the sporting participation of people with disabilities (Díaz et al., 2019).